Electrocautery vs. Stapler in Comparing Safety for Segmentectomy of Lung Cancer: A Meta-Analysis - Lu, Tianjian; Zhang, Ruoxi; Jiang, Kexin; Wang, Zihuai; Hao, Xiaohu; Chen, Nan; Liu, Lunxu (Frontiers in Surgery, 2021)
Background: Electrocautery and staplers are regarded as the two most common surgical instruments for dissecting the intersegmental plane in segmentectomy. We performed a meta-analysis to compare electrocautery and staplers in terms of their safety and effects. Methods: A systematic search strategy was performed using PubMed, and the retrieval time was up to April 1, 2020. Odds ratio (OR) and mean differences (MDs) with 95% CI were applied to determine the effectiveness of dichotomous or continuous variables, respectively. Results: Six studies including 385 patients were included. The electrocautery had a higher incidence rate of postoperative complication [OR= 1.92, 95% CI (1.12, 3.28), P = 0.02)] and air leak [OR: 3.91, 95% CI (1.64, 9.35), P = 0.002)]. No significant difference was found in the comparison of surgery time, blood loss, and duration of tube days or hospitality days. Conclusions: Our study indicated that patients under segmentectomy were associated with better safety by using stapler than electrocautery in the reduction of postoperative complications.